(3GdJLGQI GdGdcJQhfjI (B/s - (3TfGjOQ, LGQjs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2008)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B:(3GdLRA GdChd (B:(3ebOeI ddJLGQI GdGdcJQhfjI , GdHfjI GdJMJjI ddJbfjI GdGfJQfjJ hGdTHcI GdYfcHhJjI GdLRA GdKGfj (B: (3ESJQGJjLjGJ GdCYeGd ddJLGQI GdEdcJQhfjI GdHjY YHQ GdhjH , GdJShjb YHQ GdhjH , GSJQGJLjGJ ef GdCYeGd Edi GdCYeGd ef JHGOd GdHjGfGJ GdcJQhfjG Edi GdJLGQI GdGdcJQhfjI , GdeRGOGJ GdYdfjI aj GdNW GdeaJhM hGdeLJeYGJ GdG GdGaJQGVjI , hHhGHGJ GdhjH , GdJLGQI GdGdcJQhfjI (B- (3GdehQ GdbGfhfji hGdGCNdGbjI hGdVQjHjI GdLRA GdKGdK (B: (3JbfjGJ GdJLGQI GdEdcJQhfjI, fXe echfGJ NGOe GdhjH hfXe HQGeLg fXe HQGeL GdJLGQI GdGdcJQhfjI , Cef GdJLGQI GdGdcJQhfjI , fXGe GdOaY ddJLGQI GdGdcJQhfjI GdLRA GdQGHY (B: (3GdJcGed (B: (3GdJNWjW ddJLGQI GdEdcJQhfjI , eYLe GdeUWdMGJ s
Keywords: (3JLGQI GdcJQhfjIs